Characteristics of the Polyphenolic Profile and Antioxidant Activity of Cone Extracts from Conifers Determined Using Electrochemical and Spectrophotometric Methods - Malgorzata Latos-Brozio; Anna Masek; Ewa Chrzescijanska; Anna Podsędek; Dominika Kajszczak (MDPI AG, 2021)
The aim of the study was to analyze the polyphenolic profile of cone extracts of Douglas fir, Scots pine and Korean fir, and to study their antioxidant activity. The mechanism of electro-oxidation of polyphenols (such as procyanidins and catechins) from cone extracts was investigated using cyclic voltammetry (CV) and differential pulse voltammetry (DPV), as well as spectrophotometric methods-ABTS (2,2'-azinobis-(3-ethylbenzothiazoline-6-sulfonate)), DPPH (2,2-diphenyl-1-picrylhydrazyl), FRAP (Ferric Reducing Antioxidant Power ) and CUPRAC (CUPric Reducing Antioxidant Capacity). The scientific novelty of the research is the comprehensive analysis of cone extracts in terms of antioxidant properties. Due to the high polyphenol content, the extracts showed significant ability to reduce oxidative reactions, as well as the ability to scavenge free radicals and transition metal ions. Douglas fir, Scots pine and Korean fir cone extracts can potentially be used as natural stabilizers, preservatives and antimicrobial substances in the food industry and in medications.